Аэродинамические характеристики тонкого профиля с интерцептором - Ковтонюк, Игорь Борисович (НТУ "ХПИ", 2015)
На основе метода дискретных вихрей получены аэродинамические характеристики тонкого профиля с интерцептором, расположенным на нижней поверхности профиля. Для проверки достоверности результатов вычислительного эксперимента проведено сравнение полученных данных с расчетами других авторов. Проведены методические исследования влияния числа вихрей, моделирующих профиль с интерцептором, на точность определяемых аэродинамических характеристик. Проанализирована картина распределения давления при обтекании профиля с интерцептором и выявлена физическая сущность образования управляющего эффекта. Установлено, что данный орган управления является вихревым, так как управляющий эффект создается пеленой, сходящей с интерцептора.

Aerodynamic characteristics of a thin profile with a spoiler located on the lower surface of the profile are obtained on the basis of the method of discrete vortices. The data with calculations of other authors are compared to validate the results of computational experiments. Methodical studies of the effect of vortices modeling profiles with spoilers, the accuracy of the aerodynamic characteristics are defined. For a reasonable simulation accuracy is sufficient to place 7 of the vortices on the vortex profile and 3 on the spoiler. A profile mechanization as a spoiler is viewed in the numerical experiment. Spoiler positions along the chord on the lower and upper surface, the angle of spoiler deflection, spoiler chord are ranged for profiles with spoilers. It is found that the used method of calculation can simulate all the main effects caused by the rejection of profile mechanization. It is analyzed the pattern of pressure distribution in the flow profile with spoiler and revealed the physical nature of the formation of the control effect. The spoiler extension on the profile during attached flow leads to inhibition of the flow and increase the pressure on the upper surface of the front spoiler profile, increased vacuum on the lower surface of the airfoil. The pattern of the pressure distribution changes significantly in the event of separation on the front edge of the profile. Passing under the profile the control sheet creates a rarefaction zone on its lower surface, and interacting with the aft sheet, is sucked into the space above the upper surface of the profile and then carried away by the flow. It has been established that the control body is a vortex, because the control effect at the location of the front spoiler near the edge of the profile is created by powerful vortex sheet coming down from the trailing edge of the spoiler, but not the load on the spoiler.
The aerodynamic characteristics of a thin profile with spoilers
Keywords: летательные аппараты; профиль крыла; коэффициент давления; вычислительный эксперимент; метод дискретных вихрей; wing profile; aerodynamic characteristics; spoiler; pressure coefficient; computational experiment